Essays on applied welfare economics - Bandyopadhyay, Sutirtha (New Delhi: Indian Statistical Institute, 2017)
In this thesis, we explain and analyze three important and basic issues in applied welfare economics in three different chapters. Although all these three chapters pose new questions in new contexts and use different methodologies, the common theme of all these three chapters is welfare evaluation and comparing change in welfare across groups.
Introduction and Main Result -- Does Heterogeneity Affect the Group Cost of Living Index -- Border Prices, Pass-Through and Welfare: Palm Oil in India -- Poverty, Gender and Well-Being: A Study on the Slum Population in Delhi
Thesis (Ph.D.) - Indian Statistical Institute, 2017
Guided by Prof. Bharat Ramaswami
Keywords: Welfare Economics; Gender and Well-Being; Cost of Living Index; Well-Being Measures